THE EFFECT OF ONLINE LEARNING ON STRENGTHENING CHARACTER EDUCATION OF INTEGRATED ISLAMIC ELEMENTARY SCHOOL STUDENTS - Yeni Pariyatin (Jurnal Pendidikan Karakter, 2022)
The coronavirus disease pandemic has an impact on various fields of life, including education. The Integrated Islamic Elementary School in Garut Regency is one of the affected schools so that the teaching and learning process is carried out online. During online learning, schools continue to apply character values in all their activities as an effort to instill character education strengthening in students. This study aims to analyze the influence of online learning on strengthening the character education of integrated Islamic elementary school students. This type of research is descriptive with a quantitative approach. The sample used came from students in grades I-VI from two Integrated Islamic Elementary Schools in Garut Regency totaling 90 respondents. Collecting data using observation, literature study, interviews, and questionnaires. The research instrument used a Likert scale. Hypothesis test is used through t test, f test, and determinant coefficient or R Square. The results showed that there was a positive and significant influence partially online learning on strengthening the character education of integrated Islamic elementary school students. Simultaneously online learning has a significant effect on strengthening the character education of integrated Islamic elementary school students.